The effect of green finance on environmental performance: Mediating role of green innovation - Ahmadi, Hari (Journal of Management and Business Insight, 2025)
Purpose-The purpose of this study is to assess the impact of green finance on environmental performance, using green innovation as a mediating variable. Environmental performance is an important indicator in assessing how companies can reduce negative impacts on the environment through environmentally friendly policies, practices, and innovations. Green finance is a factor that can encourage an improvement in environmental performance by implementing more sustainable business practices. Methodology-This study's population was private bank employees, with a sample size of 100. It employed a quantitative methodology, utilizing partial least squares structural equation modeling with Smart PLS to investigate the relationships among variables. Findings-The findings showed a positive relationship between environmental performance and green finance. It was shown, though, that green finance does not positively influence green innovation; conversely, green innovation does have a positive effect on environmental performance. It was also shown that green innovation does not serve as a mediator between green finance and environmental performance. Research Limitations-This study's limitation is that the number of respondents is still relatively small, so it does not represent all private banking employees in Jawa Tengah, Indonesia. Thus, further studies can involve more respondents or focus on a specific region in Indonesia. Novelty-It is expected that this research will serve as a reference for banking institutions in the development of policies aimed at sustainable performance. It is anticipated that companies will highlight the significance of green finance in encouraging a more environmentally responsible business context.